Increased expression of PDGFA and RAF1 in Tumor-derived exosomes in human colorectal cancer: Elevated expression of PDGFA and RAF1 in exosomes - Vafaei, Somayeh; Yuzhen Gao; Marzieh Naseri; Zöller, Margot; Zanjani, Leili Saeednejad; Razieh Karamzadeh; Hadi Ahmadi Amoli; Marzieh Ebrahimi; Madjd, Zahra (Cellular and Molecular Biology, 2025)
The overexpression of tumor markers within Extracellular Vesicles (EVs), particularly in tumor-derived exosomes (TDEs), plays a pivotal role in metastasis in the context of colorectal cancer (CRC). Nonetheless, the precise role of EV content in CRC diagnosis and prognosis necessitates extensive validation through bioinformatics and clinical investigations. We explored molecular markers shared between TDEs and circulating tumor cells (CTCs) in the blood of cancer patients to identify candidate genes involved in metastasis. Common markers were analyzed in gene expression profiles of two studies (GSE31023 and GSE72577). The expression of candidate genes was assessed by RT-PCR in CTC, TDEs, and microvesicles (MVs), and was correlated with clinicopathological features. To further confirm, the expression of candidate genes was investigated in exosomes derived from the parental HT-29 colorectal cancer cell line (HT-29-EXOs), and cancer stem cells (CSCs) -enriched spheroids (CSC-EXOs) derived thereof. Gene ontology (GO) analysis suggested platelet-derived growth factor A (PDGFA) and proto-oncogene, Serine/Threonine kinase Raf-1 (RAF1) as new CRC candidate markers in CTCs and TDEs. Expression of PDGFA (P=0.0086) and RAF1 (P=0.048) were upregulated in TDEs but significantly decreased (P=0.0001) in MVs. Furthermore, expression in CSC-EXOs (P=0.0004) was increased compared to HT-29-EXOs. PDGFA and RAF1 mRNA are higher in CSC-EXOs than in HT-29-EXOs, which correlates with higher expression in CSC than in the primary tumor. Notably, as no increase was observed in MVs, PDGFA and RAF1 mRNA appear to be actively recruited into TDE.